2014
DOI: 10.1007/s10549-014-3235-9
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone receptor α in breast cancer: prognostic and therapeutic implications

Abstract: We determined the expression of two transcriptional variants of thyroid hormone receptor alpha (THRα1 and THRα2) in samples from a cohort of breast cancer patients and correlated expression levels with survival. 130 women who were diagnosed with invasive breast carcinoma between 2007 and 2008 were included. Representative sections of their tumours were analyzed in triplicate on a tissue microarray for expression of THRα1 and THRα2 by immunohistochemistry. The prognostic significance of THRα1 and THRα2 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 29 publications
3
39
0
2
Order By: Relevance
“…Previously, we had demonstrated that nuclear THRα2 expression tends to be an independent and favorable prognostic marker for survival in a small cohort of 82 invasive BC cases [39]. This was confirmed in another cohort of 130 invasive BC samples, where THRα2 (nuclear and cytoplasmic) negatively correlated with HER2 status, and positively with ER/PR and favorable OS [40]. In the present work, we confirmed that nuclear THRα2 was significantly correlated with a favorable prognosis.…”
Section: Discussionsupporting
confidence: 88%
“…Previously, we had demonstrated that nuclear THRα2 expression tends to be an independent and favorable prognostic marker for survival in a small cohort of 82 invasive BC cases [39]. This was confirmed in another cohort of 130 invasive BC samples, where THRα2 (nuclear and cytoplasmic) negatively correlated with HER2 status, and positively with ER/PR and favorable OS [40]. In the present work, we confirmed that nuclear THRα2 was significantly correlated with a favorable prognosis.…”
Section: Discussionsupporting
confidence: 88%
“… 22 Jerzak et al reported that the thyroid hormone receptor α ( THRα ) represented an efficient prognostic biomarker in breast cancer patients. 23 All these data indicated the pivotal role of cancer-related molecules for breast cancer prognosis. Consequently, more molecular biomarkers should be identified for prediction of prognosis in breast cancer.…”
Section: Discussionmentioning
confidence: 92%
“…In BRCA‐positive breast cancer TRα and TRβ exhibit opposing roles in prognostic survival; greater expression of TRα strongly correlates with a decrease in overall survival whereas expression of TRβ is associated with improved survival . Additionally, the isoform of TRα has been observed to be critical as expression of TRα2, a splice variant without a triiodothyronine (T 3 ) binding site, is associated with improved survival . TRα2 acts antagonistically to TRα1, which exhibits a functional LBD, by binding to TREs and blocking TRα1 from interacting with the chromatin.…”
Section: Hormone Signaling and Its Impact On Hcomentioning
confidence: 99%